Human mesenchymal amniotic fluid stem cells reveal an unexpected neuronal potential differentiating into functional spinal motor neurons - Gaggi, Giulia; Di Credico, Andrea; Guarnieri, Simone; Mariggiò, Maria Addolorata; Di Baldassarre, Angela; Ghinassi, Barbara (Frontiers in Cell and Developmental Biology, 2022)
Human amniotic fluids stem cells (hAFSCs) can be easily isolated from the amniotic fluid during routine scheduled amniocentesis. Unlike hiPSCs or hESC, they are not tumorigenic either immunogenic and their use does not rise ethical or safety issues: for these reasons they may represent a good candidate for the regenerative medicine. hAFSCs are generally considered multipotent and committed towards the mesodermal lineages; however, they express many pluripotent markers and share some epigenetic features with hiPSCs. Hence, we hypothesized that hAFSCs may overcome their mesodermal commitment differentiating into to ectodermal lineages. Here we demonstrated that by the sequential exposure to specific factors, hAFSCs can give rise to spinal motor neurons (MNs), as evidenced by the gradual gene and protein upregulation of early and late MN markers (PAX6, ISL1, HB9, NF-L, vAChT). When co-cultured with myotubes, hAFSCs-derived MNs were able to create functional neuromuscular junctions that induced robust skeletal muscle contractions. These data demonstrated the hAFSCs are not restricted to mesodermal commitment and can generate functional MNs thus outlining an ethically acceptable strategy for the study and treatment of the neurodegenerative diseases.